If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-39) + -1y = -5 Multiply 2 * -39 -78 + -1y = -5 Solving -78 + -1y = -5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '78' to each side of the equation. -78 + 78 + -1y = -5 + 78 Combine like terms: -78 + 78 = 0 0 + -1y = -5 + 78 -1y = -5 + 78 Combine like terms: -5 + 78 = 73 -1y = 73 Divide each side by '-1'. y = -73 Simplifying y = -73
| 4+03x=19 | | 27-39x=27-39x | | 8x+(1/x^2) | | x+1/2x=100 | | 7+12x-3=9x+31-6x | | -(8-7a)-(4+6a)-29=-(7-7a)+(-a)+6 | | 8x+1/x^2 | | x-25-2x=14 | | ln(2x+1)-2ln(x)=2 | | 6n+3n=90 | | -7m+21-5(m-1)=8m-(4m-3)-9m+2 | | 7/x+2=4/2x-3 | | x^2+x-3.25=0 | | 3.6+y=1 | | 4/5k-5=-7+2/3k | | x-2-6x=4 | | -[8z-(11z+9)]=9+(2z+3) | | 4m^3-10m^2= | | -2p-6(3-2p)=6(p-3)-16 | | 5x+10=-20fory | | 3x(x-2)+5(x-2)=0 | | 38x-38=38x-38 | | -8(4b+4)+(33b-9)=0 | | 5x+6(x-11)=5(x-12) | | -2=t-3s | | 62+(6x)+(6x+6)=180 | | 16s^2+72s+18=0 | | 12(-82x+26)=84(2x+62) | | 5/3x=56 | | x+5/3=56 | | 4c^2-36c=0 | | 9(3x+6)+(x+2)=11 |